AGRESI ISRAEL TERHADAP PALESTINA PERSPEKTIF HUKUM HUMANITER INTERNASIONAL - Henky Chandra (Bajang Institute, 2024)
Israel's aggression against Palestine sparked an international reaction because of the large number of casualties it caused. action, most of them were civilians. According to humanitarian law, Israel's invasion of Palestine violates the principles of humanitarian law, namely: the humanitarian principle, the restrictive principle, and the principle of distinction. Israel committed war crimes, so the international community is wondering how Israel could commit war crimes while being tried? There are three mechanisms for enforcing humanitarian law. Firstly, the parties to the contract States signatory to the Geneva Conventions must adopt all necessary legislation to provide effective criminal sanctions for persons who commit or order the commission of any of the grave violations, secondly by special courts and thirdly by the International Criminal Court, however Prosecuting Israel is quite difficult because Israel has not ratified the 1998 Rome Statute